2020
DOI: 10.1088/1674-1056/abb3f7
|View full text |Cite
|
Sign up to set email alerts
|

High performance RE–Fe–B sintered magnets with high-content misch metal by double main phase process

Abstract: Double main phase process is applied to fabricate [(Pr, Nd) 1−x MM x ] 13.8 Fe bal M 1.5 B 5.9 (x = 0.5 and 0.7; M = Cu, Al, Co, and Nb) sintered magnets with high misch metal (MM) content. In comparison to the magnets by single main phase process, the enhanced magnetic properties have been achieved. For magnets of x = 0.7, H cj increases to 371.9 kA/m by 60.5%, and (BH) max is significantly enhanced to 253.3 kJ/m 3 by 56.9%, compared with those of the single main phase magnets of the same nominal composition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…To curb the cost of permanent magnet production, the cost-effective Ce-Fe-B [1][2][3] and (La,Ce)-Fe-B [4][5][6][7][8][9] rare earth permanent magnets have attracted wide attention. Herbst et al [10,11] and Soeda et al [12] reported the hard magnetic properties of Ce 2 Fe 14 B and (La,Ce) 2 Fe 14 B compounds, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To curb the cost of permanent magnet production, the cost-effective Ce-Fe-B [1][2][3] and (La,Ce)-Fe-B [4][5][6][7][8][9] rare earth permanent magnets have attracted wide attention. Herbst et al [10,11] and Soeda et al [12] reported the hard magnetic properties of Ce 2 Fe 14 B and (La,Ce) 2 Fe 14 B compounds, respectively.…”
Section: Introductionmentioning
confidence: 99%